Do tax structure affect aggregate economic growth? Empirical evidence from a panel of Asean countries / Nur Sheila Ab Rashid - Ab Rashid, Nur Sheila (Faculty of Business Management, 2017)
Tax structures are commonly touted to have strong macroeconomic growth effects. However, taxs ystems differ widely across ASEAN countries and these variations explain part of the differences in economic performance and, differences in living standard. Tax structure has been somewhat neglected in the macroeconomic literature on fiscal policy growth, although the different in distortions created by different taxes and negative effect of tax may ultimately depends on what exactly government decided to tax. This paper investigates the effect of tax structure to promote economic growth. The study on the tax structure for selected ASEAN countries (Singapore, Malaysia, India and South Korea) towards economic growth will be obtained by using Multiple Linear Regressions (Panel Least Squares), where growth domestic product (GDP) per capita, as the dependent variable. Real property taxes, Value added taxes (VAT), Personal income taxes and corporate income taxes as the independent variable. There are several types of data that have been used in conducting this research study such as: Journal or Articles (main sources), Electronic Sources (Data online, UiTM web (Anjung) and DataStream) and internet.